The making of New Zealand cricket, 1832-1914 - Ryan, Greg, 1967- (Sport in the global society., 2003)
This book examines the emergence and growth of cricket in relation to diverse patterns of European settlement in New Zealand - such as the systematic colonization schemes of Edward Gibbon Wakefield and the gold discoveries of the 1860s.